Interobserver variation in the reporting of the histopathological grading of anal intraepithelial neoplasia. Issue 11 (November 1994) - Carter, P S; Sheffield, J P; Shepherd, N; Melcher, D H; Jenkins, D; Ewings, P; Talbot, I; Northover, J M
Abstract : AIM--To assess the consistency in the histological reporting of anal intraepithelial neoplasia (AIN) among experienced histopathologists. METHOD--One hundred anal biopsy specimens were retrieved from archival material at St Mark's Hospital, London and graded by five histopathologists according to criteria outlined by Fenger (six point scale, ranging from normal to invasive carcinoma). RESULTS--There was only moderate agreement among the pathologists, with unweighted k scores ranging from 0.09 to 0.48, and weighted k scores of 0.17 to 0.60. CONCLUSIONS--There is considerable interobserver variation in the reporting of AIN. A simplified system of grading may help to abolish this.